“Old Field”, “Regularity” and “Of Blessed Memory” Defender of the Cossacks: Justice and Antiquity as Values in the Movements of the Don Cossacks of the 17th – 18th Centuries - Nikolai Mininkov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. During the period of transition from freedom and independence during the time of the Moscow state, the Don Cossacks experienced the process of their formation as a military estate of the Russian Empire and constantly fought for justice in relations with the Russian authorities. This is how the transition to the status of the service class of the Russian Empire took place. Justice found the realization through an attitude towards antiquity, which was recognized as corresponding to justice, and to novelty, which was perceived as a violation of justice, but over time, it became a new tradition that corresponded to ideas of justice. Methods. Modern historical research is characterized by a reliance on a value-based approach for analyzing specific phenomena and processes of the past. Such an analysis makes it possible to identify the presence of significant social value and its realization in certain historical conditions. Justice was such a value for the Don Cossacks. Analysis and results. The Don Cossacks defended the traditions of the “old field” during the Bulavin Rebellion and persistently resisted threats of conversion to “regularity” in the second half of the 18th century for justice and observance of the traditions of Cossack antiquity in the organization of resettlement to the Caucasian line. A value-based approach to the study of the history of the Don Cossacks allows us to fully, deeply, and precisely achieve understanding of the community itself about new living conditions, its attitude towards them, and its perception of changes when correlating them with its idea of justice as a social value.